1992
DOI: 10.1002/pen.760321405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyethylene molecular structure on peroxide crosslinking of low density polyethylene

Abstract: The effects of molecular structure on the dicumyl peroxide crosslinking of two low density polyethylenes have been studied. Peroxide efficiency was determined largely by the content of terminal vinyls in the two polymers. Differences in molecular weight distribution and branch content had comparatively little influence on the gel content but hot creep resistance of the vulcanized materials was affected. Scorching was affected, also, by the presence of vinyl unsaturations in the polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…To explain this transformation, a proposed reaction mechanism is presented in Figure 5; other researchers have proposed a similar mechanism. 11,28 The first step in the reaction involves decomposition of the peroxide to form alkoxy radicals that are capable of hydrogen abstraction. Abstraction is believed to occur at one of two places along the 1-dodecene backbone, at either a secondary or an allylic carbon; the secondary position shown in Figure 5 is arbitrarily chosen, and abstraction could equally occur at other secondary positions.…”
Section: -Dodecenementioning
confidence: 99%
See 1 more Smart Citation
“…To explain this transformation, a proposed reaction mechanism is presented in Figure 5; other researchers have proposed a similar mechanism. 11,28 The first step in the reaction involves decomposition of the peroxide to form alkoxy radicals that are capable of hydrogen abstraction. Abstraction is believed to occur at one of two places along the 1-dodecene backbone, at either a secondary or an allylic carbon; the secondary position shown in Figure 5 is arbitrarily chosen, and abstraction could equally occur at other secondary positions.…”
Section: -Dodecenementioning
confidence: 99%
“…However, there is disagreement concerning the exact mechanism by which the terminal unsaturation is involved. In a series of articles, Bremner et al 10,11 suggested that an allylic radical coupling mechanism is responsible for the unexpected increase in the amount of crosslinked material, whereas other researchers have proposed a polymerizationbased mechanism. 12,13 In an analysis of the products from a polymer melt grafting reaction, the ultimate fate of the terminal unsaturation is difficult to determine by NMR because of inherently low concentrations in the polymer and by Fourier transform infrared (FTIR) because of potential band overlap with the grafted monomer.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular peroxides, dicumyl peroxide (DCP), is very effective in introducing long‐chain branches in linear PEs, and at low concentrations, it favorably alters MWD . At higher peroxide concentrations, crosslinked PE is obtained . DCP is a popular choice because of its favorable decomposition rate at normal processing temperatures of PE .…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, [6,7] the same authors proposed a mechanism where allylic hydrogen atoms in terminal vinyl groups are preferentially abstracted. Lachtermacher and Rudin [8 -11] reactively extruded different LLDPEs with peroxide.…”
Section: Introductionmentioning
confidence: 99%